The Effect of Distribution Channel Utilization of Folding Tent Sales Volume in CV. Jalapari Motor Makassar - Ade Muharram; Aris Baharuddin; Novayanti Sopia Rukmana (Public Resource Innovation Management and Excellence, 2025)
This study aims to determine how the description and influence the effect of distribution channel utilization of folding tent sales volume in CV. Jalapari Motor Makassar. To achieve this goal, the researchers used indicators to measure these variables. On distribution channel variables, the indicators are used is the services provided by intermediary, the presence of desired intermediary and the intermediary's attitude towards company policies. As for the sales volume variables, indicators are used is to reach a certain level of sales, achieve a certain sales profit and can support the company's growth. This study uses quantitative research methods. Data collection techniques used are through observation, questionnaires and documentation. The population in this study were all of reseller who are affiliated with CV. Jalapari Motor Makassar in terms of sales of folding tent products, totaling 41 people. The sampling technique used in this study is the Non-probability sampling, with the type of Staurated sampling or census, so that the entire population is used as a sample of 41 respondents. The data obtained from the research results were processed using data analysis and SPSS 25 application which consisted of validity and reliability tests, descriptive statistical data analysis techniques and inferential statistical analysis. The results of this study indicate that the indicators used in each distribution channel and sales volume are in the very good categories. Based on the determinant coefficient test, there is a significant effect between the two variables, which is 36,1%. Based on the simple linear regression coefficient, it shows a positive value, so it can be said that the direction of the influence of the variable X on Y is positive. So, it can be concluded that there is a significant positive effect between distribution channel on sales volume.